Transition-Metal-Catalyzed Directing-Group-Assisted C4-H Carbon–Carbon Bond Formation of Indole - Basak, Shubhajit; Paul, Tripti; Maharana, Prabhat Kumar; Debnath, Bijoy; Punniyamurthy, Tharmalingam (Synlett, 2022)
C4-Functionalized indole scaffolds are ubiquitous in natural products, bioactive compounds, and pharmaceuticals. Much effort has thus been made to develop effective synthetic strategies for C4 functionalization of the indole core. Among them, chelation-assisted synthetic approaches using transition-metal catalysis for the C4-selective C–H functionalization of indole is attractive. This account highlights progress made in C4-carbon–carbon bond formation of indole using directing-group-assisted transition-metal-catalyzed C–H functionalization (up to May 2022). These studies have been performed using Ru, Rh, Pd and Ir-based catalytic systems, while attention has been focused on the use of first-row abundant catalytic systems.1 Introduction2 Alkylation3 Acylation4 Alkenylation5 Alkynylation6 Allylation7 Annulation8 Arylation9 Conclusion and Outlook
Keywords: indole; C4-H functionalization; transition-metal catalysis; directing group; carbon–carbon bond formation